T cell-specific overexpression of TGFß1 fails to influence atherosclerosis in ApoE-deficient mice. - Kurt Reifenberg (Public Library of Science (PLoS), 2013)
Clinical data have indicated a negative correlation between plasma TGFß1 concentrations and the extent of atherosclerosis and have thus led to the hypothesis that the pleiotropic cytokine may have anti-atherogenic properties. T-cells are currently discussed to significantly participate in atherogenesis, but the precise role of adaptive immunity in atherogenesis remains to be elucidated. TGFß1 is known to strongly modulate the function of T-cells, however, inhibition of TGFß1 signalling in T-cells of atherosclerosis-prone knock-out mice failed to unequivocally clarify the role of the cytokine for the development of atherosclerosis. In the present study, we thus tried to specify the role of TGFß1 in atherogenesis by using the murine CD2-TGFß1 transgenic strain which represents a well characterized model of T-cell specific TGFß1 overexpression. The CD2-TGFß1 transgenic mice were crossed to ApoE knock-out mice and quantity and quality of atherosclerosis regarding number of macrophages, smooth muscle cells, CD3 positive T-cells and collagen was analyzed in CD2-TGFß1 ApoE double mutants as well as non-transgenic ApoE controls on both normal and atherogenic diet of a duration of 8, 16 or 24 weeks, respectively. In all experimental groups investigated, we failed to detect any influence of TGFß1 overexpression on disease. Total number of CD3-positive T-lymphocytes was not significantly different in atherosclerotic lesions of CD2-TGFß1 ApoE(-/-) females and isogenic ApoE(-/-) controls, even after 24 weeks on the atherogenic diet. The synopsis of these data and our previous study on TGFß1 overexpressing macrophages suggests that potential effects of TGFß1 on atherosclerosis are most probably mediated by macrophages rather than T-cells.